Has a Mother’s Role been Substituted? A Study of Mother’s Empathy toward their Young Children in Jakarta - Rizkyanti, Charyna Ayu (Advances in Social Sciences Research Journal, 2019)
Regardless of woman status (whether a housewife or a career woman), the number of mothers who need to employ nannies are increased, particularly in Jakarta. In consequence, the mother’s empathy is needed to detect each changes that could potentially harm children’s physical and psychological healthiness relationship due to different caregivers explain this sentence. The current research aims to investigate mother’s empathy toward their young children in Jakarta, Indonesia. A total of 250 mothers who have children under the age of seven completed the empathy scale that was adapted from The Basic Empathy Scale (BES) by Jolliffe and Farrington (2006). There were 88 mothers with nannies and 159 mothers without nannies participated in this research. All mothers were divided into three categories of working status, i.e full-time mothers (60%), full-time working mothers (32.8%) and part-time working mothers (6.8%). The result revealed that there is significant difference of affective empathy between mothers who have nannies compared to mothers with no nannies. Mothers without nannies were found having higher affective empathy than mothers with nannies. In addition, there is also a difference of cognitive empathy between full time mothers and working mothers where full time mothers show higher mean score than working mothers. This finding implies the significancy of attachment between mothers and children relationship in the interest of developing mothers’ empathy. Through attachment, mothers with nannies might elevate their skill to emphatize both cognitively and affectively, thus, mothers could identify and understand their children’s need more accurately. Keywords: mothers, empathy, affective-cognitive empathy, nannies